Revolutionizing Insurance: The Impact of AI on Claims Processing - Balakrishna Sudabathula (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
The insurance industry is undergoing a fundamental transformation through the integration of artificial intelligence technologies, particularly in claims processing. This comprehensive article examines how AI-driven solutions are revolutionizing traditional claims-handling workflows, from initial submission to final settlement. The implementation of machine learning algorithms, computer vision, and natural language processing has enabled insurers to automate routine tasks while enhancing accuracy and efficiency. These technologies facilitate real-time fraud detection, automated document verification, and intelligent data extraction from various sources. The article explores the technical framework of AI-driven claims processing, system integration challenges, and the crucial aspects of maintaining fairness and transparency in automated decision-making. Additionally, the article analyzes the impact on operational efficiency and customer experience, highlighting how AI implementation has transformed service delivery and customer interaction models. It also investigates emerging trends and future developments, including edge computing and blockchain integration, while addressing the challenges of balancing automation with human oversight in the evolving insurance landscape.
Keywords: Artificial Intelligence in Insurance; Claims Process Automation; Machine Learning Fraud Detection; Explainable AI; Digital Insurance Transformation